The Influence of Service Quality of Apparatus on Community Satisfaction in the Testing Unit of Motorized Vehicles for Types of Goods Transport in Sidoarjo Regency - Maulany Sukma Arum Habibah; Isnaini Rodiyah (Indonesian Journal of Public Policy Review, 2022)
Customer (community) satisfaction is the main measure of public services. The problem with KIR testing at the District Transportation Office. Sidoarjo, namely the attitude of the apparatus that still does not act quickly and precisely in helping every complaint from the drivers, then the community is not satisfied with the KIR testing service. The purpose of this study is to determine and analyze the effect of the quality of service of the apparatus on community satisfaction in the unit testing motorized vehicles for the type of freight transport at the Transportation Service Office of Sidoarjo Regency. This research is a quantitative research, the sample in this study amounted to 95 respondents with a simple random sampling sampling technique, data collection techniques using observation methods, questionnaires. The data analysis technique used multiple linear regression analysis and hypothesis testing including T-test, F-test, Coefficient of Determination. The results show that the Transparency Dimension has a significant influence on community satisfaction, the accountability dimension has a significant influence on community satisfaction, the conditional dimension has a significant influence on community satisfaction, the participatory dimension has a significant influence on community satisfaction, the equal rights dimension has a significant influence on community satisfaction. the balance of rights and obligations has a significant influence on people's satisfaction